Spray-induced gene silencing enables the characterization of gene function during pre-penetration stages in Blumeria graminis f. sp. tritici - Zhang, Meihui; Zhou, Meijiao; Jia, Yunmeng; Li, Xipeng; Wang, Aolin; Liu, Taiguo; Zhou, Yilin; Liu, Wei; Fan, Jieru (Frontiers in Plant Science, 2025)
Blumeria graminis f. sp. tritici (Bgt), the causal agent of wheat powdery mildew, poses a significant threat to global wheat production. As an obligate biotroph, Bgt is recalcitrant to stable genetic manipulation. Although host-induced gene silencing has been used for gene function studies, it remains ineffective for targeting genes active during pre-penetration stages. Consequently, the functional roles of many Bgt genes during pre-penetration stages remain largely unexplored. In this study, the feasibility of spray-induced gene silencing (SIGS) to characterize gene function during pre-penetration stages was evaluated. The results demonstrated that Bgt conidia and germ tubes efficiently took up environmental double-stranded RNA (dsRNA), enabling the targeted silencing of BgtActin. Exogenous application of BgtActin-dsRNA effectively reduced target gene expression and impaired infection of Bgt. BgtActin silencing predominantly induced abnormal appressoria and reduced disease severity when dsRNA was applied at 6 and 10 hours post-inoculation (hpi). In contrast, BgtActin was almost not silenced when dsRNA was applied at 2 hpi. These findings established SIGS as a promising tool for gene functional studies during the pre-penetration stages of Bgt and highlight the potential of RNA-based strategies for the control of wheat powdery mildew.